Vitreoretinal Lymphoma as the Initial Presentation of a Breast Diffuse Large B-cell Lymphoma. (September 2022) - Martin, Cole A.; Admirand, Joan H.; Ghafoori, Shelley Day
Purpose: We report a case of vitreoretinal lymphoma as the initial presentation of diffuse large B-cell lymphoma of the breast. Methods: A case report is presented. Results: A 72-year-old woman was referred for evaluation of vitritis in both eyes. Diagnostic vitrectomy and pathology workup demonstrated atypical lymphoid cells consistent with the presence of diffuse large B-cell lymphoma. Brain magnetic resonance imaging and lumbar puncture findings were negative for central nervous system lymphoma. Positron emission tomography/computed tomography imaging showed a mass in the left breast, and breast biopsy confirmed aggressive B-cell lymphoma. Conclusions: When vitreoretinal lymphoma is diagnosed, it is important to evaluate for other forms of systemic lymphoma in addition to central nervous system lymphoma.